EXPLORING THE TRANSITION OF SMART ELECTRICITY USERS TO GREEN CONSUMERS: AN OPEN KNOWLEDGE MAPS ANALYSIS - Pasaribu, Johni Paul Karolus; Johannes, Johannes; Yacob, Syahmardi; Octavia, Ade (Management Department, Faculty of Economics and Business, Universitas Jambi, 2024)
The era of technology and smart electricity is a technological advancement for households that use smart electricity. This research aims to discover the potential of smart electricity users to become green consumers. Therefore, we use the Open Knowledge Map platform to find out the behaviour of smart electricity users using cluster visualisation. The data used are research papers from 2013 to 2022. Hence, we found 11 clusters of related articles. The main focus of the research cluster is the social behaviour, construction user, and consumer behaviour cluster, which is related to green consumer behaviour from the behaviour of households using smart electricity. Furthermore, we have confirmed the potential household smart electricity users to become green consumers. Therefore, we have a construction related to the potential of smart electricity user households to become green consumers for further research.